PESAN DAKWAH DAN NILAI-NILAI SPIRITUALITAS DALAM TARI RODAT KUNTULAN DI SEMARANG - Hasan Maftuh; Imam Subqi; M. Mustoliq Alwi (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2021)
The rodat dance, which is not favored by many young people, will gradually become extinct, while in its history the media of preaching to ground Islam through culture. The purpose of this study is: (1) to determine the spiritual values of the rodat kuntulan dance, (2) to determine the message of da'wah in the activities of the rodat kuntulan dancers, (3) to determine the socio-religious impact. The research used in this study was a qualitative research approach and these results indicated that: (1) there were seven movements in the spiritual value of the rodat dance, first was the opening movement depicting a person's humility and politeness, second was greeting movements, such as the prayer movement teaching humans to be closer to Allah SWT, third was strolling movements such as the zikir movement as an invitation to contemplate the purpose of living close to Allah, fourth was the movement of horses, this meant that humans must have a firm and strong character, fifth was, the movement of ablution, meaning the order to clean oneself, sixth was the movement of menthul-menthul and carrying hands means soul knight, seventh, the closing movement was interpreted as the full time where the living human would definitely experience death. (2) the message of the da'wah in the rodat paguyuban rodat laklada dance, was in the song to remember the living. The message of preaching through this verse was an invitation to humans to be aware of death. (3) the socio-religious impact was manifested in a sense of solidarity within the community and became part of the da'wah because it contained Islamic sya'ir which provided advice